Elucidation of target implant orientations with the safety range of hip rotation with adduction or abduction during squatting: Simulation based on in vivo replaced hip kinematics - Harada, Satoru; Hamai, Satoshi; Ikebe, Satoru; Hara, Daisuke; Higaki, Hidehiko; Gondo, Hirotaka; Kawahara, Shinya; Shiomoto, Kyohei; Harada, Tetsunari; Nakashima, Yasuharu (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: To elucidate target cup orientations and stem anteversions to avoid impingement between the liner and stem neck even at hip rotation with adduction during the deeply flexed posture. Methods: A computer simulation analysis was performed on 32 total hip arthroplasty patients applying patient-specific orientation of the components and in vivo hip kinematics obtained from three-dimensional analysis of the squatting motion. The anterior/posterior liner-to-neck distance and impingement were evaluated based on a virtual change of internal/external rotation (0°–60°) and adduction/abduction (0°–20°) at actual maximum flexion/extension during squatting. Cutoff values of cup orientations, stem anteversion and combined anteversion to avoid liner-to-neck impingements were determined. Results: Anterior liner-to-neck distance decreased as internal rotation or adduction increased, and posterior liner-to-neck distance decreased as external rotation or adduction increased, respectively. Negative correlations were found between anterior/posterior liner-to-neck distances at maximum flexion/extension and internal/external rotation. Anterior/posterior liner-to-neck impingements were observed in 6/18 hips (18/56%) at 45° of internal/external rotation with 20° of adduction. The range of target cup orientations, stem anteversion and combined anteversion to avoid both anterior and posterior liner-to-neck impingements during squatting were 15°–18°, 19°–34°, and 41°–56°, respectively. Conclusions: Simulated hip rotations caused prosthetic impingement during squatting. Surgeons could gain valuable insights into target cup and stem orientations based on postoperative simulations during the deeply flexed posture.